Utilitarianism, trust, and online purchase intentions on Shopee application user - Diki (Universitas Negeri Padang, 2023)
This study has the aim of analyzing the influence of utilitarianism and trust on online purchase intentions on the Shopee application in meditation by attitudes towards online purchasing. This research has a population of online shopping consumers in Padang City who have never used Shopee to shop. This study used samples taken using the Purposive Sampling technique with a sample of 150 online shopping consumers in 2023. This research was analyzed using SmartPLS 4.0. With the following research results: (1) utilitarianism has a significant and positive effect on attitudes toward online purchases. (2) Trust has a significant and positive effect on attitudes towards online purchases. (3) Attitudes towards online purchases have a significant and positive effect on online purchase intentions. (4) Utilitarian has a significant and positive effect on online purchase intentions through attitudes towards online purchases. (5) Trust has a significant and positive effect on online purchase intentions through attitudes towards online purchases.